Retrospective Analysis of the Factors Affecting Growth Parameters in Turkish Children With Systemic Lupus Erythematosus - Sibel BALCI; Rabia Miray KIŞLA EKİNCİ and Engin MELEK and Aysun KARABAY BAYAZIT and Dilek DOĞRUEL and Derya UFUK ALTINTAŞ and Mustafa YILMAZ (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the growth parameters in Turkish children with systemic lupus erythematosus (SLE) and to compare these growth parameters according to the presence or absence of cyclophosphamide, rituximab treatment, cumulative corticosteroid dose, proliferative nephritis, and the last visit disease activity and damage index. Patients and methods: Medical data, growth parameters including z-scores for weight, height, and body mass index and parent-adjusted height z-scores of 45 juvenile SLE (jSLE) patients (5 males, 40 females; mean age 12.3±3.2 years; range 7.1 to 18 years) were retrospectively evaluated. Growth parameters were calculated by anthropometric references in Turkish children. The disease activity was assessed by the SLE Disease Activity Index 2000 (SLEDAI-2K). The disease outcome was measured by the Pediatric version of Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index. Results: The median diagnostic delay was two months (range, 0-36 months). The median follow-up duration was 3.21 years (range, 0.63-9.48 years). Mean height z-score was significantly lower at last visit than at the time of diagnosis. The growth parameters did not differ according to age at disease onset, diagnostic delay, presence of proliferative nephritis, having cyclophosphamide and rituximab treatment and the last visit (SLEDAI-2K) scores. The median duration of corticosteroid treatment was 3.2 years (range, 0.6-9.4 years) and the median cumulative corticosteroid dosage was 13.9 g (range, 1.9-58 g) of methylprednisolone. The mean height z-score at last visit was significantly lower in those who received at least 10 g of cumulative dose of corticosteroid. The last visit mean parent-adjusted height z-scores did not differ significantly regarding the cumulative corticosteroid dose. Conclusion: The last visit height and parent-adjusted height z-scores of jSLE patients were significantly lower. The patients treated with at least 10 g of cumulative dose of corticosteroids had lower mean height z-score.